Peran Suami dalam Menentukan Kesejahteraan Subjektif Istri pada Saat Hamil dan Melahirkan - Sudirman, Sudirman; Puspitawati, Herien; Muflikhati, Istiqlaliyah (Jurnal Ilmu Keluarga dan Konsumen, 2019)
Optimization of family functions can be realized by dividing tasks for each family member as an effort to improve the health and nutrition status of pregnant women so that they can reduce maternal and infant mortality in Indonesia. The objective of this study is to analyze the influence of the role of husband on the subjective well-being of wife with newborn baby. The study design used a cross sectional study and carried out in Tuppu Health Center, Lembang Subdistrict, Pinrang Regency, South Sulawesi Province by involving 110 wives in intact families and was having children up to 6 months of age; selected using simple random sampling method. Data were collected through interviews using questionnaires then were analyzed by descriptive and multiple regression test. The results of the study found that the average role of husbands when his wife was pregnant and  giving birth is in the low category, especially in the dimensions of domestic roles and social roles. Wife's subjective well-being is in the medium category. Family typology based on husband's role and wife's subjective well-being when was pregnant and  giving birth are mostly classified into type 2. Meanwhile, the duration of husband's education, family income and husband's role in domestic role and social role dimensions have a significant positive effect on subjective well-being of wife with newborn baby.